Synthesis and characterization of PVP coated gadolinium oxide nanoparticles for imaging applications - Thi Thuy Khue, Nguyen; Thi Thanh Tam, Le; Thanh Dung, Ngo; Thi Ngoc Linh, Nguyen; Tuan Dung, Nguyen; The Tam, Le; Trong Lu, Le (Vietnam Journal of Science and Technology, 2024)
In this work, we present the synthesis and applications of Gd2O3@PVP nanoparticles as an efficient contrast agent for MRI and CT techniques. Gd2O3@PVP nanoparticles have been successfully synthesized by the polyol method using ethylene glycol and poly(vinylpyrrolidone) as solvent and surfactant, respectively. The structure, morphology and characteristic properties of the materials are thoroughly investigated by SEM, TEM, UV-Vis, XRD, FTIR and DLS measurements. As an important result, NPs synthesized under optimized conditions have a diameter in the range of 12 nm and exhibit a good contrast signal in magnetic resonance imaging and computed tomography at relatively low concentration ([NPs] = 0.1 mM for MRI and 1.25 mg.mL-1 for CT). In particular, the concentration of Gd2O3@PVP nanoparticles used in CT is 10 times lower than that of the commercial Iobitridol product (i.e., 12.5 mg.mL-1) to achieve similar signal intensity. This result has an important implication for reducing the dose of contrast agent introduced into the body. The obtained results suggest that PVP-coated Gd2O3 nanoparticles can be applied as multifunctional contrast agents for imaging diagnostic applications in the near future.